Combined enhancement effects of static magnetic field (SMF) and a yeast Candida tropicalis SYF‐1 on continuous treatment of Acid Red B by activated sludge under hypersaline conditions. Issue 3 (5th December 2019) - Tan, Liang; Mu, Guangdi; Shao, Yifan; Ning, Shuxiang; Shi, Shengnan
Abstract: BACKGROUND: Large amounts of wastewater containing azo dyes and salts (e.g. from textile and dyeing processes) are produced each year, which need appropriate treatment before discharge. In the present study, combined enhancement effects of static magnetic field (SMF) and a halotolerant yeast Candida tropicalis SYF‐1 on continuous treatment of Acid Red B (ARB) under hypersaline conditions (containing 30 g L −1 NaCl) were estimated in a sequencing batch reactor (SBR). The dynamics of the microbial community was also analyzed. RESULTS: Removal percentages of ARB concentration, chemical oxygen demand (COD) and acute toxicity in the yeast–SMF co‐enhanced SBR (named as MSF‐SBR) were finally stabilized at about 98.0, 98.2 and 72.9% respectively, which were the highest among all SBRs. MSF‐SBR also possessed the highest biomass concentration (∼7462.1 mg L −1 ) and the best sludge settleability. Higher activities of nicotinamide adenine dinucleotide‐dependent dichlorophenol indophenol (NADH‐DCIP) reductase, lignin peroxidase (LiP) and manganese peroxidase (MnP) in MSF‐SBR were determined as responsible for higher degradation and detoxification efficiency. Bacterial genus Defluviimonas was putatively enriched in MSF‐SBR, which might be responsible for detoxification of aromatic intermediates. Candida was identified as the most dominant fungal genus in MSF‐SBR with a total relative abundance of 8.15%, which was responsible for effective dye degradation and detoxification. CONCLUSION: MSF‐SBR displayed higher and more stable treatment efficiency of ARB under hypersaline and continuous operation conditions. This study may provide a potentially applicable method for coping with purification of hypersaline industrial wastewaters. © 2019 Society of Chemical Industry